Pelatihan Dan Pemanfaatan Teknologi Cloud Untuk Penyimpanan DiKoperasi Serba Usaha Komunitas Warga Bojong Gede (KSU KOWAGE) - Ade Priyatna; Eko Setia Budi; Eva zuraidah; Sanwani; Siti Indriane Maebari; Jodi Setiawan; Agung Primahadi Asta; Damar Nugraha; Rizky Maulana Ambya (Forum Kerjasama Pendidikan Tinggi, 2023)
The Bojong Gede Residents Community Multi-Business Cooperative (KSU KOWAGE) is a cooperative institution founded with the spirit of togetherness and a sense of desire to form a business but is constrained by limitations such as small business capital, and weak human resources. It is difficult to access information & technology as well as sources of capital. Currently, KOWAGE KSU has several products that have been marketed both offline and online, there are several obstacles related to their activities, one of which is related to storing images of several products to then make catalogs and cooperative activities which later can be distributed and used anytime and anywhere, one of the technologies that can be used for storage is using cloud technology from Google, namely Google Drive, by utilizing and using this technology KSU KOWAGE can store its products and cooperative activities anytime and anywhere, providing directly create google drive and also a cloud-based data storage method which is quite popular including Google Drive, and knowing this cloud technology starts from the utilization, use, and function of the application features, directly from each participant's cellphone, the one day workshop method